Plaque Formation at the Left Coronary Artery: Analysis of the Relationship Between Arterial Angulations and Hemodynamics - Chachaina, T.; Sun, Zhonghua; Wong, K.; Tu, J. (ACTA Press, 2010)
We investigate the relationship between coronary angulations and their hemodynamic effect. Six left coronary models were generated based on the anatomical details of patient specific data. Varying angles at 90°, 75°, 60°, 45°, 30° and 15° between the left anterior descending and the left circumflex branches are simulated. Numerical simulation is used to analyse flow velocity, wall pressure and wall shear stress under normal physiological conditions of human body in different cardiac cycles. Our results showed that the wall shear stress was significantly decreased in models of higher angulations. In contrast, high wall pressure occurred at coronary bifurcation regions with those models. Our preliminary study demonstrates that there is direct relationship between angulations at the left coronary artery and development of atherosclerosis.